Voices of Indonesian Manufacturing Workers in Rotating Shift Systems - Henny Permatasari; Junaiti Sahar; Muchtarrudin Mansyur; Astrid Widayati Hardjono (Jurnal Keperawatan Indonesia, 2022)
The factors associated with changes in work patterns and working hours due to rotating shifts have an effect on the increased risk of health problems in workers. Manufacturing industry workers, specifically those on rotating shift schedules, are at a high risk of various health problems, such as cardiovascular diseases, circadian rhythm problems, social life problems, and stress. These health problems may be worsened by poor lifestyle habits, such as smoking, unhealthy diet, and infrequent physical activity. This research aimed to explore the experience of 12 manufacturing workers on rotating shift schedules in Greater Jakarta, Indonesia. Through a phenomenological approach, this qualitative study employed 12 participants selected from manufacturing industry shift workers. The participants were selected through purposive sampling whom met the inclusion criteria, namely working in three rotating shift patterns (morning, afternoon, and night shift), aged 20–50 years old, having at least three years of experience in shift work, and able to communicate well. Selection was done with the assistance of the supervisors of the participants working in the manufacturing industry. Thematic analysis yielded three themes: the reasons for working shifts, the effects of shift work, and efforts made to maintain health during working shifts. The findings of this study imply the need for occupational health nursing services as the main intervention at the primary and secondary prevention levels. Occupational health nurses provide occupational health nurs-ing services in the workplace in accordance with the nursing intervention model of fatigue management.   Abstrak Suara Pekerja Manufaktur Indonesia dalam Sistem Shift Berputar. Dalam sistem kerja shift, faktor-faktor seperti perubahan pola kerja dan jam kerja dapat berdampak pada masalah kesehatan para pekerjanya. Pekerja shift manufaktur berisiko memiliki berbagai masalah kesehatan, seperti penyakit kardiovaskuler, gangguan irama sirkadian, gangguan pola kehidupan sosial, stres, didukung oleh perilaku pekerja seperti merokok, diet yang buruk serta aktivitas olah raga yang jarang dilakukan. Penelitian ini bertujuan untuk mengeksplorasi pengalaman para 12 pekerja di sector manufaktur di Indonesia, khususnya di daerah Jakarta dan sekitarnya. Peneliti menggunakan metode penelitian kualitatif dengan pendekatan fenomenologi. Partisipan berjumlah 12 didapatkan melalui teknik purposive sampling yang memenuhi kriteria inklusi: menggunakan sistem kerja rotasi tiga shift (pagi, sore, dan malam), berusia 20–50 tahun, memiliki pengalaman bekerja sistem rotasi shift minimal tiga tahun, dan mampu berkomunikasi dengan baik. Proses pemilihan partisipan dilakukan peneliti bersama key person, yaitu supervisor/leader dari beberapa pabrik manufaktur. Analisis tematik yang dilakukan menghasilkan tiga tema: alasan bekerja shift, dampak dari kerja shift, dan upaya para pekerja dalam menjaga status kesehatan. Temuan dari penelitian ini dapat menjadi implikasi bagi kesadaran terhadap perlunya tenaga kesehatan atau perawat di area kerja atau sektor industri sebagai upaya intervensi utama dan sekunder dalam pencegahan kecelakaan kerja untuk para pekerja dan keluarga pekerja melalui model keperawatan manajemen kelelahan kerja (MARI-KERJA). Kata Kunci: kerja shift, pekerja manufaktur, perawat kesehatan kerja, sistem berputar